Slide roof system for dynamic response reduction. - Tian, Zhichang (Earthquake engineering & structural dynamics.)
A slide roof system (SRS) is proposed to reduce the dynamic response of buildings to earthquake excitations. A SRS consists of a roof structure, springs and friction materials, providing mass, stiffness and damping, respectively. The method of optimization of stiffness and friction coefficient for the SRS is introduced. A numerical analysis of an eight story frame structure subjected to ground motions and shaking table tests of a five story frame was carried out to study the effectiveness of the SRS. The results show that the SRS can reduce the maximum dynamic response as much as 60-70 percent in the first resonate band and 35-50 percent in the second resonate band.